Defluoridation by fluorapatite crystallization in a fluidized bed reactor under alkaline groundwater condition. (1st November 2020) - Deng, Linyu; Wang, Ying; Zhang, Xiao; Zhou, Jianqi; Huang, Tinglin
Abstract: Fluoride removal using fluidized bed crystallization (FBC) technology with phosphate rock (PR) and calcite as seed particles under an alkaline groundwater condition was investigated. The results indicated that the optimized operating parameters were: upflow velocity = 7.21 m h −1, Ca:P:F molar ratio = 10:4:1, and initial bed height = 120 cm. The turbidity of FBC reactor effluent was 1.5–5.9 NTU at the first phase, and then reduced to less than 1.0 NTU at the second phase, while the effluent fluoride level remained at a constant level (0.4–0.9 mg L −1 ) during the entire procedure. The exfoliation and dissociation of newly-generated nuclei from the seed particles surfaces after aging and drying for three days could serve as an additional filtration layer (located on the top of the expanded bed with a thickness of 1.0 cm) to intercept the fine particles in the second phase. Consequently, a rational strategy for fluidized bed operation was provided, which focused on turbidity control and fluoride removal. FBC performance can be divided into ripening and running periods according to the evolution of turbidity in effluent. Fluoride removal was achieved by the formation of amorphous calcium phosphate and then recrystallization into fluorapatite and/or FCO3 -apatite and induced crystallization of fluorapatite and/or FCO3 -apatite. The FBC process with additional filtration function of dissociated newly-generated nuclei could be regarded as a cleaner technology for fluoride removal; additionally, the spent seed particles could be utilized as resources in the phosphatic fertilizer industry. However, the fertilizer industry should continue to recover fluoride for further economic benefits. Graphical abstract: Image 1 Highlights: FBC effectively resulted in effluent F − < 1.0 mg L −1 from alkaline groundwater. Turbidity in effluent from FBC was stable <1.0 NTU during entire running period. Exfoliated and dissociated fluorapatite/FCO3 -apatite enhanced turbidity intercept. F − was removed by crystallization/recrystallization of fluorapatite/FCO3 -apatite. Calcite and HCO3 − gave positive effects on fluoride removal in the FBC process.